Soil Quality of Different Land Use Systems in Southern Transect of Bengaluru, Karnataka - Altaf Kuntoji; C.T. Subbarayappa; A. Sathish; V. Ramamurthy; B.C. Mallesha (Journal of the Indian Society of Soil Science, 2023)
The land-use greatly influences soil quality and affects the nutrient dynamics. The present study was conducted to identify the most appropriate soil quality indicators and to evaluate the impact of four most prevalent land use types on soil quality in the southern transect of Bengaluru. Principal component analysis (PCA) was performed to get the minimum data set that best represents soil quality. Fifty soil samples were collected from each land use system includes agriculture (L1), horticulture (L2), mulberry (L3) and plantation lands (L4). The soil was examined for sand, silt, clay, soil pH, organic carbon (OC), electrical conductivity (EC), available nitrogen (N), phosphorus (P), potassium (K), exchangeable calcium (Ca), magnesium (Mg), sulphur (S), micronutrients (Zn, Fe, Mn, Cu and B) and dehydrogenase activity (DHA). The results of PCA showed that five principal components (PCs) having eigen values > 1 and explained 72.9% cumulative variation in the entire data set. The OC, pH, Mg, P, Zn and clay were selected as the most appropriate key indicators of soil quality based on their rotated factor loadings and then selected indicators were converted into scores by linear scoring method and soil quality index (SQI) was worked out. Agricultural land use (0.60) recorded the greater SQI, followed by horticulture (0.56), mulberry (0.53) and lower SQI was recorded in plantation land use (0.50). Thus, all the land use systems are fall under the medium category soil quality (0.50-0.75) in southern transect of Bengaluru.